Luminescent Eu3+-doped transparent alumina ceramics with high hardness. Issue 14 (November 2017) - Drdlikova, Katarina; Klement, Robert; Hadraba, Hynek; Drdlik, Daniel; Galusek, Dusan; Maca, Karel
Abstract: The Eu 3+ -doped transparent aluminas were prepared by wet shaping technique followed by pressure-less sintering and hot isostatic pressing. The effect of dopant amount on microstructure, real in-line transmission (RIT), photoluminescence (PL) properties, hardness and fracture behaviour was studied. The RIT decreased with increasing amount of the dopant. The PL emission spectra of Al2 O3 :Eu 3+ ceramics exhibited predominant red light emission with the highest intensity (under 394 nm excitation) for material containing 0.125 at.% of Eu 3+ and colour coordinates (0.645, 0.355) comparable with commercial red phosphors. The doping resulted in hardness increase from 26.1 GPa for undoped alumina to 27.6 GPa for Eu-doped sample. The study of fracture surfaces showed predominantly intergranular crack propagation micro-mechanism.